Genetic population structure in the swimming crab, Portunus trituberculatus and its implications for fishery management. (2nd October 2018) - Hui, Min; Shi, Guohui; Sha, Zhongli; Liu, Yuan; Cui, Zhaoxia
Abstract: Information on the genetic population structure of economic species is important for understanding their evolutionary processes and for management programmes. In this study, the genetic structure of 12 P. trituberculatus populations along the China seas and Japan was analysed. A fragment of mitochondrial control region was sequenced as a genetic marker in swimming crabs sampled from the Bohai Sea, Yellow Sea, East China Sea, South China Sea and Japan, with dense sampling in the Bohai Sea. These populations showed an intermediate and significant genetic population structure, with an overall Φst value of 0.054 ( P < 0.01). Based on a hierarchical AMOVA, they could be divided into two groups, the South China Sea population and all the other populations. The distribution of the haplotypes and the pairwise Φst values between populations indicated a high level of gene flow among most populations in the Bohai Sea, Yellow Sea, East China Sea and Japan. However, low but significant genetic differentiation ( P < 0.05) was also detected among several populations in these areas. Many details of the genetic structure were revealed, especially for the populations in the semi-enclosed Bohai Sea, and the inconsistency with previous studies was discussed. The structure patterns indicate that sea-level changes during the glacial period of the Pleistocene and oceanographic factors are important in shaping the genetic population structure of swimming crabs. Finally, the implications for fishery are suggested.